A pilot study promoting participation of families with limited resources in early autism intervention. (May 2016) - Carr, Themba; Lord, Catherine
Highlights: Barriers to intervention are a significant problem for families with limited resources. Low income and low education families are underrepresented in intervention research. Practical modifications to intervention protocols increase participant engagement. Abstract: Background: Relatively little research about autism early intervention has occurred in families of low socioeconomic status. Barriers to participation for under-resourced families (i.e., families with low incomes or limited education), pose a significant problem. The purpose of this pilot study was to apply empirically supported methods promoting participation of families with low-income and low-education levels to an established intervention for children with autism spectrum disorder (ASD). Method: Participant recruitment specifically targeted families whose income was equal to or below two times the federal poverty line and whose caregiver(s) had no more than two years of college attendance. An evidence-based intervention was modified to be more accessible to participating families. Adaptations focused on decreasing access barriers, decreasing attrition, and promoting positive change within families. Success of the program was measured quantitatively and qualitatively. Results: Twenty-seven families were referred to the project, 13 of which did not meet eligibility requirements. Eight families enrolled, maintained participation for the majority of the project and provided positive qualitative feedback of their experiences. Project and treatment attrition were calculated at 62% and 12.5%, respectively. Treatment attendance was high, but length of time to complete treatment was greatly influenced by the number of session cancellations. Conclusions: The exploratory project demonstrated that practical modifications to standard early intervention protocols can promote engagement in families with limited resources. Recommendations for programs seeking to implement interventions in under-resourced communities are discussed.